The Role of Strategic Leadership in Mediating the Improvement of the Organizational Performance of the Indonesian Navy Military Sea Lift Command Warship - Trismoyo, Yudah; Arafah , Willy; Anggiani, Sarfilianty (Journal of Management, Economic, and Financial, 2025)
This research aims to analyze the influence of esprit de corps, organizational climate, and professionalism on organizational performance in the Indonesian Navy Military Sea Lift Command Warship, with both direct and indirect effects mediated by strategic leadership. This research employs a quantitative approach with hypothesis testing to examine the relationships between independent, dependent variables and the effect of mediating variables. Data collection is cross-sectional through primary data sources in the form of questionnaires distributed online to 147 respondents from the population of officers in the Indonesian Navy Military Sea Lift Command Warship. The sampling technique uses the total sampling, while data analysis uses Partial Least Square–Structural Equation Model Version 3.0. A total of ten hypotheses were tested in this study, with results showing significant direct effects of esprit de corps, organizational climate, professionalism, and strategic leadership on organizational performance. On the other hand, indirect effects were observed through the role of strategic leadership as a significant mediating variable that links esprit de corps, organizational climate, and professionalism to organizational performance. The most significant direct effect was found in the relationship between organizational climate and strategic leadership, while the strongest indirect effect occurred with the organizational climate’s influence on organizational performance through the mediation of strategic leadership. Future research could expand the variables or explore other factors influencing organizational performance, with a larger sample size and a qualitative or mixed-method approach.